Long-term estrogen deprivation changes the response to antianxiety drugs in mice in the elevated plus maze test. (2nd December 2019) - Xu, Hongdan; Li, Wei; Zhang, Bo; Huang, Shuming; Liu, Xuewei
Abstract: Estrogen deficiency increases the incidence of female anxiety disorders; however, whether estrogen deficiency alters responses to anxiolytic drugs is unknown. We studied whether long-term estrogen deprivation (ovariectomy, OVX) changes the behavior of mice to anxiolytic drugs (buspirone, diazepam, and venlafaxine), using the elevated plus maze (EPM) test. The percentages of EPM open-arm time and EPM open-arm entries of the OVX mice decreased significantly compared to control, and sham mice 2 months after OVX. The response to buspirone increased in the OVX mice at 1 week, while OVX decreased the response to diazepam at 2 months. Moreover, we found the efficacy of diazepam was significantly decreased, compared to buspirone and venlafaxine, at 2 months. These results suggest that OVX may change responses to different anxiolytic drugs. Not all anti-anxiety drugs appear to be suitable for anxiety caused by estrogen deficiency.